Analisis kecenderungan Manhaj Akidah Shaykh Shams al-Din al-Sumatera’i - Mohd Haidhar Kamarzaman,; Abdull Rahman Mahmood, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2016)
Shaykh Shams al-Din al-Sumatera'i is a very great and respected scholar during 16th and 17th century of Acheh. His knowledge in various fields recognized by local and international scholars. He had been a Qadi Malik al-’Adil, a religious leader, who became a referred by communities and country during the reign of the three Sultans of Aceh. He has authored nearly 40 pieces of books related to the theology and sufism. This study focuses on the methods used by Shaykh Shams al-Din al-Sumatera'i in his theological writings. This study found that Shaykh Shams al-Din al-Sumatera'i had used six methods in the such writings.